Furan polyester material for 3D printing and preparation method thereof
By polymerizing 2,5-furandicarboxylic acid and 1,4-butanediol and blending with poly2,5-furandicarboxylate, the furan polyester material for 3D printing was prepared, solving the problem of poor mechanical and thermal properties of existing 3D printing materials, and achieving high-performance, low-carbon and environmentally friendly 3D printing materials.
Patent Information
- Application Number
- CN202411740292.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-07
AI Technical Summary
The mechanical and thermal properties of existing 3D printed materials are poor, and they also rely on petroleum resources, making the environment non-renewable.
A furan polyester material for 3D printing was prepared by polymerizing 2,5-furandicarboxylic acid with 1,4-butanediol to form polybutanediol 2,5-furandicarboxylate and blended with polyethylene 2,5-furandicarboxylate.
The prepared furan polyester material has high mechanical strength and glass transition temperature, good moldability and low shrinkage. It is suitable for 3D printing and is a green, low-carbon environmentally friendly material.
Smart Images

Figure CN119570211A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of bio-based polyester preparation, and in particular to a furan polyester material for 3D printing and a preparation method thereof. Background Art
[0002] Polyester is a polymer containing -COO-ester groups on the main chain. Its synthetic monomers are diverse and inexpensive. Through structural design, it can have widely adjustable properties. It has excellent comprehensive performance and huge production capacity. It has a wide range of application scenarios in plastics, fibers, elastomers, adhesives, plasticizers, coatings and other fields.
[0003] In recent years, the scale application of polyester has been expanding, but most polyesters are derived from petroleum, which has caused the increasing scarcity of traditional petroleum resources and severe environmental pollution problems to a certain extent. In order to alleviate the pressure on resources and the environment, finding new biomass renewable resources to replace existing fossil resources will be the trend of green development in the future. Therefore, the development of biomass-derived bio-based materials has gradually attracted strong attention from the society.
[0004] As an important bio-based platform compound, 2,5-furandicarboxylic acid is derived from biomass resources and can be synthesized by conversion from sugar as raw material. It has a five-membered aromatic ring structure and has similar structure and physical properties to terephthalic acid. It can be used to develop new environmentally friendly bio-based furan polyester materials. Bio-based furan polyester has good mechanical properties, thermal properties and excellent barrier properties, and can largely replace existing polyester products based on petroleum terephthalic acid. However, due to the technical bottleneck of 2,5-furandicarboxylic acid monomer, the large-scale production and application of bio-based furan polyester is still in the initial climbing stage. Most of the research focuses on polyethylene 2,5-furandicarboxylate (PEF) and polybutylene 2,5-furandicarboxylate (PBF). The variety of materials is relatively limited. At the same time, PEF has the disadvantages of slow crystallization and brittleness, and PBF has a lower glass transition temperature and mechanical strength. It is limited by the use scenario. These factors are not conducive to the in-depth development of bio-based furan polyester.
[0005] In recent years, 3D printing technology has developed rapidly and has been widely used in medicine, construction, toys, aerospace and other fields. There are many different 3D printing processes. The fused deposition modeling (FDM) printing process has gradually become the most widely used process due to its wide range of materials, low cost, and convenient and fast printing process. At present, the main polymer materials used in 3D printing are PLA, ABS, PA, PCL, etc. With the development of the times, society has higher and higher requirements for material varieties and performance. At the same time, considering that FDM-type 3D printing technology still has many problems to be solved, such as poor mechanical properties of printing materials, poor thermal properties, and excessive dependence on petroleum resources. Therefore, it is our goal to prepare new 3D printing polymer materials that are bio-based, have good thermal stability and mechanical properties.
[0006] Based on the above analysis, the development of furan polyester materials for 3D printing is of great significance for actively promoting the development of bio-based furan polyester, broadening its application scenarios, and achieving low-carbon and environmental protection goals. Summary of the invention
[0007] 1. Technical issues to be resolved
[0008] The technical problem to be solved by the present invention is that the current 3D printing materials have poor mechanical properties, poor thermal properties, and the printing materials are overly dependent on petroleum resources, causing environmental non-renewable problems.
[0009] (II) Technical solution
[0010] In order to solve the above technical problems, the present invention adopts the following technical solutions.
[0011] On the one hand, the present invention provides a furan polyester material for 3D printing, comprising the following raw materials in parts by weight: 100 parts of 2,5-furandicarboxylic acid, 90-180 parts of 1,4-butanediol, 0.1-0.5 parts of a polymerization catalyst, 25-400 parts of polyethylene 2,5-furandicarboxylate, and 0.5-3 parts of an antioxidant.
[0012] The polymerization catalyst is selected from at least one of tetrabutyl titanate, isopropyl titanate, antimony glycol, antimony trioxide, germanium oxide, and zinc acetate; preferably, the polymerization catalyst is tetrabutyl titanate.
[0013] The antioxidant is selected from at least one of antioxidants 1010, 1076, and 168.
[0014] Furthermore, the intrinsic viscosity of the polyethylene 2,5-furandicarboxylate is 0.65-0.75 dL / g.
[0015] On the other hand, the present invention also provides a method for preparing a furan polyester material, comprising the steps of:
[0016] S1. Adding 2,5-furandicarboxylic acid, 1,4-butanediol and a polymerization catalyst into a closed polymerization reactor for polymerization reaction to prepare a polybutylene 2,5-furandicarboxylate melt;
[0017] S2. The polybutylene 2,5-furandicarboxylate melt obtained in S1 is fed into a twin-screw extruder connected to the discharge port of the closed polymerization reactor, the polybutylene 2,5-furandicarboxylate melt enters the twin-screw extruder through a main feed port, and poly(ethylene 2,5-furandicarboxylate) and an antioxidant are added through an auxiliary feed port of the twin-screw extruder to perform melt blending, extrusion and granulation to obtain a furan polyester material.
[0018] Furthermore, the furan polyester material is extruded by a single-screw extruder, prepared into a wire with a diameter of 1.7-1.8 mm by a traction machine, and then a 3D printing device is used to prepare a 3D printed product.
[0019] Further, the polymerization reaction in step S1 includes:
[0020] Under an inert atmosphere, firstly heating to a first temperature and performing an esterification reaction under normal pressure;
[0021] Raising the temperature to a second temperature and evacuating the chamber to react;
[0022] The temperature is then raised to the third temperature, and the system vacuum pressure is maintained below 100 Pa for 1-2 hours to complete the polymerization reaction.
[0023] Further, the first temperature is 170-190°C, the second temperature is 200-210°C, and the third temperature is 220-230°C;
[0024] Furthermore, the esterification reaction time is 2-3 hours, and the vacuum reaction time is 1-2 hours.
[0025] Furthermore, in step S2, the polyethylene 2,5-furandicarboxylate is dried before use, the drying temperature is 110-130° C., and the drying time is 12-24 hours.
[0026] Furthermore, in step S2, the extrusion processing temperature of the twin-screw extruder is 230-250°C, and the rotation speed is 80-200rpm.
[0027] Furthermore, the extrusion processing temperature of the single-screw extruder is 210-240° C., and the pulling speed is 20-50 m / min.
[0028] The present invention also provides an application of the furan polyester material of the present invention in 3D printing.
[0029] (III) Beneficial effects
[0030] The above technical solution of the present invention has the following advantages:
[0031] The present invention polymerizes 2,5-furandicarboxylic acid and 1,4-butanediol to generate poly(butylene 2,5-furandicarboxylate), and then blends and extrudes the poly(butylene 2,5-furandicarboxylate) melt with poly(ethylene 2,5-furandicarboxylate) in two steps to prepare a bio-based furan polyester material. The preparation process reduces the granulation, drying and remelting steps of poly(butylene 2,5-furandicarboxylate), that is, the modification of poly(butylene 2,5-furandicarboxylate) is achieved. The prepared furan polyester material belongs to a green, low-carbon and environmentally friendly material. Compared with poly(butylene 2,5-furandicarboxylate) (PBF), the furan polyester material prepared by the present invention has both higher mechanical strength and glass transition temperature. The furan polyester material prepared by the present invention is used for 3D printing, and the obtained product has the advantages of good formability, low shrinkage and easy processing, which is conducive to the promotion and development of furan polyester. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a DSC test comparison chart of the furan polyester materials prepared in Examples 1 and 2 of the present invention and the polybutylene 2,5-furandicarboxylate material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0033] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0034] The invention provides a furan polyester material for 3D printing, comprising the following raw materials in parts by weight: 100 parts of 2,5-furandicarboxylic acid, 90-180 parts of 1,4-butanediol, 0.1-0.5 parts of a polymerization catalyst, 25-400 parts of polyethylene 2,5-furandicarboxylate, and 0.5-3 parts of an antioxidant.
[0035] The polymerization catalyst is selected from at least one of tetrabutyl titanate, isopropyl titanate, antimony glycol, antimony trioxide, germanium oxide, and zinc acetate; preferably, the polymerization catalyst is tetrabutyl titanate;
[0036] The antioxidant is selected from at least one of antioxidants 1010, 1076, and 168.
[0037] Furthermore, the intrinsic viscosity of the polyethylene 2,5-furandicarboxylate is 0.65-0.75 dL / g.
[0038] On the other hand, the present invention also provides a method for preparing a furan polyester material, comprising the steps of:
[0039] S1. Adding 2,5-furandicarboxylic acid, 1,4-butanediol and a polymerization catalyst into a closed polymerization reactor for polymerization reaction to prepare a polybutylene 2,5-furandicarboxylate melt;
[0040] S2. The polybutylene 2,5-furandicarboxylate melt obtained in S1 is fed into a twin-screw extruder connected to the discharge port of the closed polymerization reactor, the polybutylene 2,5-furandicarboxylate melt enters the twin-screw extruder through a main feed port, and poly(ethylene 2,5-furandicarboxylate) and an antioxidant are added through an auxiliary feed port of the twin-screw extruder to perform melt blending, extrusion and granulation to obtain a furan polyester material.
[0041] Furthermore, the furan polyester material is extruded by a single-screw extruder, prepared into a wire with a diameter of 1.7-1.8 mm by a traction machine, and then a 3D printing device is used to prepare a 3D printed product.
[0042] Further, the polymerization reaction in step S1 includes:
[0043] Under an inert atmosphere, firstly heating to a first temperature and performing an esterification reaction under normal pressure;
[0044] Raising the temperature to a second temperature and evacuating the chamber to react;
[0045] The temperature is then raised to the third temperature, and the system vacuum pressure is maintained below 100 Pa for 1-2 hours to complete the polymerization reaction.
[0046] Further, the first temperature is 170-190° C., the second temperature is 200-210° C., and the third temperature is 220-230° C.; and / or,
[0047] Furthermore, the esterification reaction time is 2-3 hours, and the vacuum reaction time is 1-2 hours.
[0048] Furthermore, in step S2, the polyethylene 2,5-furandicarboxylate is dried before use, the drying temperature is 110-130° C., and the drying time is 12-24 hours.
[0049] Furthermore, in step S2, the extrusion processing temperature of the twin-screw extruder is 230-250°C, and the rotation speed is 80-200rpm.
[0050] Furthermore, the extrusion processing temperature of the single-screw extruder is 210-240° C., and the pulling speed is 20-50 m / min.
[0051] Example 1
[0052] The present embodiment provides a furan polyester material for 3D printing, and the raw materials for preparation are: in parts by mass, 100 parts of 2,5-furandicarboxylic acid, 116 parts of 1,4-butanediol, 0.2 parts of tetrabutyl titanate, 25 parts of polyethylene 2,5-furandicarboxylate, and 1 part of antioxidant 1010.
[0053] The intrinsic viscosity of polyethylene 2,5-furandicarboxylate used in this example is 0.65 dL / g.
[0054] The preparation of the furan polyester material for 3D printing provided in this embodiment specifically comprises the following steps:
[0055] (1) Polymerization reaction: 2,5-furandicarboxylic acid, 1,4-butanediol and tetrabutyl titanate are added to a closed polymerization reactor, mixed and stirred evenly, heated to 180°C under an inert atmosphere, and subjected to esterification reaction at normal pressure for 2 hours, then heated to 200°C, and simultaneously subjected to vacuum reaction for 1 hour, and finally heated to 225°C, and reacted for 1.5 hours under the condition that the system vacuum pressure was less than 100 Pa to complete the polymerization;
[0056] (2) Co-blending and extrusion: The polybutylene 2,5-furandicarboxylate melt obtained by the above polymerization is introduced into a connected twin-screw extruder through a lower discharge port, and dried polyethylene 2,5-furandicarboxylate and antioxidant 1010 are added through an auxiliary feeding port, and melt-blending, extruding and granulating are performed at a processing temperature of 235° C. and a rotation speed of 150 rpm to obtain a furan polyester material;
[0057] Further 3D printing was performed: the furan polyester chips obtained above were extruded in a single-screw extruder at 230°C and towed by a traction machine at a speed of 30 m / min to prepare wires with a diameter of 1.75 mm, and then related product models were prepared with the help of 3D printing equipment.
[0058] Example 2
[0059] The present embodiment provides a furan polyester material for 3D printing, and the raw materials for preparation are: in parts by mass, 100 parts of 2,5-furandicarboxylic acid, 133 parts of 1,4-butanediol, 0.3 parts of tetrabutyl titanate, 100 parts of polyethylene 2,5-furandicarboxylate, and 10102 parts of an antioxidant.
[0060] The intrinsic viscosity of polyethylene 2,5-furandicarboxylate used in this example is 0.70 dL / g.
[0061] The preparation of the furan polyester material for 3D printing provided in this embodiment specifically comprises the following steps:
[0062] (1) Polymerization reaction: 2,5-furandicarboxylic acid, 1,4-butanediol and tetrabutyl titanate were added to a closed polymerization reactor, mixed and stirred evenly, heated to 185°C under an inert atmosphere, and esterification reaction was carried out at normal pressure for 3 hours, then heated to 200°C, and vacuumed for 1.5 hours, and finally heated to 230°C, and reacted for 2 hours under the condition that the system vacuum pressure was less than 100 Pa to complete the polymerization;
[0063] (2) Co-blending and extrusion: The polybutylene 2,5-furandicarboxylate melt obtained by the above polymerization is introduced into a connected twin-screw extruder through a lower discharge port, and dried polyethylene 2,5-furandicarboxylate and antioxidant 1010 are added through an auxiliary feeding port, and melt-blending, extruding and granulating are performed at a processing temperature of 240° C. and a rotation speed of 120 rpm to obtain a furan polyester material;
[0064] Further 3D printing was performed: the furan polyester chips obtained above were extruded in a single-screw extruder at 235°C and towed by a traction machine at a speed of 30 m / min to prepare wires with a diameter of 1.75 mm, and then related product models were prepared with the help of 3D printing equipment.
[0065] Example 3
[0066] The present embodiment provides a furan polyester material for 3D printing, and the raw materials for preparation are: in parts by mass, 100 parts of 2,5-furandicarboxylic acid, 162 parts of 1,4-butanediol, 0.4 parts of tetrabutyl titanate, 300 parts of polyethylene 2,5-furandicarboxylate, and 10763 parts of an antioxidant.
[0067] The intrinsic viscosity of polyethylene 2,5-furandicarboxylate used in this example is 0.75 dL / g.
[0068] The preparation of the furan polyester material for 3D printing provided in this embodiment specifically comprises the following steps:
[0069] (1) Polymerization reaction: 2,5-furandicarboxylic acid, 1,4-butanediol and isopropyl titanate were added to a closed polymerization reactor, mixed and stirred evenly, heated to 190°C under an inert atmosphere, and esterification reaction was carried out at normal pressure for 3 hours, then heated to 200°C, and vacuumed for 1.5 hours, and finally heated to 230°C, and reacted for 2 hours under the condition that the system vacuum pressure was less than 100 Pa to complete the polymerization;
[0070] (2) Co-blending and extrusion: The polybutylene 2,5-furandicarboxylate melt obtained by the above polymerization is introduced into a connected twin-screw extruder through a lower discharge port, and dried polyethylene 2,5-furandicarboxylate and antioxidant 1076 are added through an auxiliary feeding port, and melt-blending, extruding and granulating are performed at a processing temperature of 250° C. and a rotation speed of 100 rpm to obtain a furan polyester material;
[0071] Further 3D printing is performed: the furan polyester chips obtained above are extruded in a single-screw extruder at 240°C and pulled by a traction machine at a speed of 40 m / min to prepare wires with a diameter of 1.7 mm, and then related product models are prepared with the help of 3D printing equipment.
[0072] Comparative Example 1
[0073] The difference between this comparative example and Example 1 is that no co-extrusion is performed, and only polybutylene 2,5-furandicarboxylate material is prepared. The specific raw materials, by mass, are: 100 parts of 2,5-furandicarboxylic acid, 116 parts of 1,4-butanediol, and 0.2 parts of tetrabutyl titanate.
[0074] The specific preparation process is:
[0075] Add 2,5-furandicarboxylic acid, 1,4-butanediol and tetrabutyl titanate into a closed polymerization reactor, mix and stir evenly, heat to 180°C under an inert atmosphere, and carry out esterification reaction at normal pressure for 2 hours, then heat to 200°C, and simultaneously carry out vacuum reaction for 1 hour, finally heat to 225°C, and react for 1.5 hours under the condition that the system vacuum pressure is lower than 100 Pa to obtain poly (butylene 2,5-furandicarboxylate) material.
[0076] The furan polyester materials prepared in the above examples and the poly(butylene 2,5-furandicarboxylate) material prepared in Comparative Example 1 were subjected to glass transition temperature and tensile standard tests, respectively.
[0077] The glass transition temperature test adopts the DSC test method, that is, first heating up, then cooling down, and finally heating up, and recording the secondary heating curve;
[0078] The standard tensile test process follows the national standard GB / T 1040.2-2022 method, and the tensile speed is controlled at 20mm / min.
[0079] The DSC test graphs of the furan polyester material prepared in Example 1 and Example 2 of the present invention and the polybutylene 2,5-furandicarboxylate material prepared in Comparative Example 1 are shown in FIG. Figure 1 shown.
[0080] The glass transition temperature test results and tensile strength results are shown in Table 1 below.
[0081] Table 1
[0082] Tg / ℃ Tensile strength / MPa Example 1 50.1 51.1 Example 2 82.7 64.9 Example 3 77.3 81.7 Comparative Example 1 40.0 38.2
[0083] Combination Figure 1 As can be seen from Table 1, compared with Comparative Example 1 (PBF material), the furan polyester materials prepared in each embodiment have higher glass transition temperature and tensile strength, which indicates that the method of directly introducing poly 2,5-furandicarboxylic acid butylene glycol melt into a twin-screw extruder and blending and modifying with poly 2,5-furandicarboxylic acid ethylene glycol is feasible, and the performance of the prepared furan polyester material is improved compared with PBF, mainly because PBF and PEF are homologous materials, and the two have good compatibility. The material prepared thereby can neutralize and eliminate the shortcomings of the two, focusing on improving the glass transition temperature and mechanical strength of PBF, improving the use scenario of PBF, and being used for subsequent 3D printing, with the advantages of easy molding and good shrinkage. The furan polyester materials prepared in each embodiment have different Tg and tensile strength, which is related to the mass fractions of PBF and PEF.
[0084] It should be clear that the various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. For the embodiments of the method, the relevant parts can refer to the partial description of the device embodiment (adopted according to the writing situation). The present invention is not limited to the specific steps and structures described above and shown in the figures. In addition, for the sake of simplicity, a detailed description of known method technologies is omitted here.
[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A furan polyester material for 3D printing, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of 2,5-furandicarboxylic acid, 90-180 parts of 1,4-butanediol, 0.1-0.5 parts of polymerization catalyst, 25-400 parts of polyethylene 2,5-furandicarboxylate and 0.5-3 parts of antioxidant.
2. The furan polyester material according to claim 1, characterized in that The polymerization catalyst is selected from at least one of tetrabutyl titanate, isopropyl titanate, antimony glycol, antimony trioxide, germanium oxide, and zinc acetate. Preferably, the polymerization catalyst is tetrabutyl titanate; and / or, The antioxidant is selected from at least one of antioxidants 1010, 1076, and 168.
3. The furan polyester material according to claim 1, characterized in that The intrinsic viscosity of the polyethylene 2,5-furandicarboxylate is 0.65-0.75 dL / g.
4. A method for preparing the furan polyester material according to any one of claims 1 to 3, characterized in that: Includes steps: S1. Adding 2,5-furandicarboxylic acid, 1,4-butanediol and a polymerization catalyst into a closed polymerization reactor for polymerization reaction to prepare a polybutylene 2,5-furandicarboxylate melt; S2. The polybutylene 2,5-furandicarboxylate melt obtained in S1 is fed into a twin-screw extruder connected to the discharge port of the closed polymerization reactor, the polybutylene 2,5-furandicarboxylate melt enters the twin-screw extruder through a main feed port, poly(ethylene 2,5-furandicarboxylate) and an antioxidant are added through an auxiliary feed port of the twin-screw extruder, and melt-blending, extrusion and granulation are performed to obtain a furan polyester material.
5. The preparation method according to claim 4, characterized in that: The furan polyester material is extruded by a single-screw extruder, prepared into a wire with a diameter of 1.7-1.8 mm by a tractor, and then a 3D printing device is used to prepare a 3D printed product.
6. The preparation method according to claim 4 or 5, characterized in that: The polymerization reaction in step S1 includes: Under an inert atmosphere, firstly heating to a first temperature and performing an esterification reaction under normal pressure; Raising the temperature to a second temperature and evacuating the chamber to react; The temperature is then raised to the third temperature, and the system vacuum pressure is maintained below 100 Pa for 1-2 hours to complete the polymerization reaction.
7. The preparation method according to claim 6, characterized in that: The first temperature is 170-190° C., the second temperature is 200-210° C., and the third temperature is 220-230° C.; and / or, The esterification reaction time is 2-3 hours, and the vacuum reaction time is 1-2 hours.
8. The preparation method according to claim 4, characterized in that: In step S2, the extrusion processing temperature of the twin-screw extruder is 230-250°C, and the rotation speed is 80-200rpm.
9. The preparation method according to claim 5, characterized in that: The extrusion processing temperature of the single screw extruder is 210-240° C., and the pulling speed is 20-50 m / min.
10. Use of the furan polyester material according to any one of claims 1 to 3 in 3D printing.